No change in sight Togo’s Political and Socio-Economic Development (2017 – 2019) - Kohnert, Dirk (My University, 2019)
Backed by peaceful but undemocratic presidential (2010, 2015) and legislative (2013) elections the Gnassingbé regime consolidated its power. In view of the absolute majority of the ruling party, its inclination for meaningful constitutional and electoral reforms, as demanded by the opposition and international donors, was further reduced. Overriding concerns for stability in West Africa in view of growing Islamist threats in neighbouring countries made that the delayed democratic reforms, including the time and again reported local elections, were condoned by the donor community. However, simmering discontent of the hardliners among the security forces and the barons of the ruling party was still visible. The opposition tried in vain to overcome its divide between its moderate and radical wing. An alliance of opposition parties and civic groups opposed the regime peacefully by frequent, often violently suppressed demonstrations with little effect. Arson attacks on the markets of Lomè and Kara in January 2013 served as pretense to harass opposition leaders. Human rights records of the government remained tarnished. The tense political climate persisted in view of the upcoming presidential elections in April 2015 and the apparent determination of the President to stay in power a third and eventually even a fourth term whatever the cost. Despite undeniable improvements of the framework and outside appearance of major institutions of the regime during the survey period it remained a façade democracy. However, the international community, notably African peers, the AU and ECOWAS, but also the Bretton-Woods Institutions, China and the EU, followed a ‘laissez faire’ approach in the interest of stability and their proper national interest in dealings with the country. Economic growth perspectives remained promising, expected to increase to 6.0% in 2014 and 6.3% in 2015, last but not least because of heavy assistance by the international donor community. However, growth is neither sustainable nor inclusive. It is overshadowed by increasing inter-personal and regional inequality as well as an upturn in extreme poverty
Supplemental Materials: https://osf.io/kf6ze/
Keywords: democratization; governance; fragile states; political and socio-economic development; development co-operation; EU; Togo; West Africa; ECOWAS